Escherichia coli dominance and antimicrobial resistance in urinary tract infections among diabetic patients: Insights from Birnin Kebbi Metropolis, Nigeria - Almustapha, Adamu Aliero; Yari, Haruna Abdullahi; Ibrahim, Ahmad Bagudo; Manga, Sule Sahabi; Tomo, Farida Abubakar; Muhammad, Amina; Muhammad, Muhammad Shamsudeen (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: The global rise in antibiotic-resistant urinary tract infections (UTIs) is a growing concern, particularly among diabetic patients. This study examines the antibiotic resistance patterns of bacterial uropathogens in diabetic patients at Sir Yahaya Memorial Hospital in Birnin Kebbi. Methods: A purposive sampling approach was used to collect 51 mid-stream urine samples in sterile containers. Cultural and biochemical methods were employed for the isolation and identification of uropathogenic bacteria. Antibiotic sensitivity testing was performed using the disc diffusion method, with results interpreted according to the Clinical Laboratory Standards Institute (CLSI) guidelines. Results: UTIs were prevalent in 23.5% (12/51) of the samples. Escherichia coli was the most prevalent uropathogen, accounting for 41.3% (7/17) of cases, followed by Klebsiella pneumoniae at 23.5% (4/17). Staphylococcus aureus and Proteus mirabilis each contributed to 17.6% (3/17) of cases. Notably, E. coli and K. pneumoniae exhibited 100% resistance to chloramphenicol and sparfloxacin, respectively. Conclusion: These findings underscore the need for further molecular research to characterize these uropathogens and identify the genes contributing to antibiotic resistance.